Forward-backward algorithm (FB) is a particular case of a dynamic programming. This algorithm is well known in the context of Hidden Markov Models (HMM) where it is used for training and inference, Kalman Smoothers and Connectionist Temporal Classification (CTC). It consists of two passes: the first pass goes forward in time and second pass goes backward, hence the name.

FB algorithm heavily relies on Markov property and output independence assumptions from HMM. Actually a lot of terms here are inherited from HMM, so if you’re not familliar then this HMM tutorial might come in handy.

Suppose that \(z=\{z_1,z_2,..,z_n\}\) is hidden variable, $x={z_1,z_2,..,z_n}$ is observable variable and $k=1..n$ denotes timestep, then

- \(p(x_k\vert z_k)\) is an Emission probability;
- $p(z_k\vert z_{k-1})$ is a Transition probability;
- $p(z_1)$ is an Initial probability.

To simplify the notation let’s further assume that hidden state variable $z_i$ defined on an interger set ${1,..,m}$

The goal of FB algorithm is to compute $p(z_k\vert x)$.

The forward pass computes: $p(z_k,x_{1:k}) \forall k=1,..,n$

The backward pass computes: $p(x_{k+1:n} \vert z_k) \forall k=1,..,n$

For now let’s assume that we’ve already computed forward and backward parts, in other words we know $p(z_k,x_{1:k})$ and $p(x_{k+1:n} \vert z_k)$. How does it help us to get desired $p(z_k\vert x)$?

\[\begin{align} p(z_k\vert x) \propto p(z_k,x) &= p(z_k, x_{1:k}, x_{k+1:n}) \\ &= p(x_{k+1:n}\vert x_{1:k}, z_k) p(z_k, x_{1:k}) \\ &= p(x_{k+1:n}\vert z_k) p(z_k, x_{1:k}) \end{align}\]The last step applies D-separation rule ($x_{k+1:n}$ is conditionally independent of $x_{1:k}$ given $z_k$). After simplification we have:

\[p(z_k\vert x) \propto p(x_{k+1:n}\vert z_k) p(z_k, x_{1:k})\]And we already know that $p(z_k, x_{1:k}), p(x_{k+1:n}\vert z_k)$ can be found with forward and backward algorithms. The proportionality is instead of equality is due to omitting normalizing constant $p(x)$ which we can compute by marginalizing $p(x,z_k)$ over all finite set of $z_k$: \(p(x) = \sum_{z_{k}=1}^{m} p(x,z_k)\)

## Forward algorithm

\[\begin{align} p(z_k, x_{1:k}) &= \sum_{z_{k-1}=1}^{m} p(z_k,z_{k-1},x_{1:k}) \\ &= \sum_{z_{k-1}=1}^{m} p(x_k\vert z_k,z_{k-1},x_{1:k-1}) p(z_k\vert z_{k-1},x_{1:k-1}) p(z_{k-1},x_{1:k-1}) \\ &= \sum_{z_{k-1}=1}^{m} p(x_k\vert z_k) p(z_k\vert z_{k-1}) p(z_{k-1},x_{1:k-1}) \end{align}\]- $p(x_k\vert z_k)$ is given as an emission probability
- $p(z_k\vert z_{k-1})$ is given as a transition probability
- $p(z_{k-1},x_{1:k-1})$ is unknown, but you can notice the recurrence here if you’ll look at what we are trying to compute: $p(z_k, x_{1:k})$

To find $p(z_k, x_{1:k})$ we need to compute $p(z_{k-1},x_{1:k-1})$, for $p(z_{k-1},x_{1:k-1})$ you have to compute $p(z_{k-2},x_{1:k-2})$ and so on until $p(z_{1},x_{1})$. And $p(z_{1},x_{1})$ is just an emission probability that is known. Now we know all the parts to achieve our goal finding $p(z_k, x_{1:k})$.

What about time complexity? We have $n$ timesteps ($k=1..n$) and inside each timestep we iterate over $m$ values of $z_k$ and $m$ values of $z_{k-1}$, this gives us $O(nm^2)$ time complexity.

## Backward algorithm

\[\begin{align} p(x_{k+1:n}\vert z_k) &= \sum_{z_{k+1}=1}^{m} p(x_{k+1:n}, z_{k+1} \vert z_k) \\ &= \sum_{z_{k+1}=1}^{m} p(x_{k+2:n} \vert x_{k+1}, z_{k+1}, z_k) p(x_{k+1}\vert z_{k+1}, z_k) p(z_{k+1}\vert z_k) \\ &= \sum_{z_{k+1}=1}^{m} p(x_{k+2:n} \vert z_{k+1}) p(x_{k+1}\vert z_{k+1}) p(z_{k+1}\vert z_k) \end{align}\]- $p(x_{k+2:n} \vert z_{k+1})$ can be computed recurrently
- $p(x_{k+1}\vert z_{k+1})$ is given as an emission probability
- $p(z_{k+1}\vert z_{k})$ is given as a transition probability

We compute $p(x_{k+2:n} \vert z_{k+1})$ recurrently until we reach $p(x_n\vert z_{n-1})$. We can do the same routine as previously:

\[\begin{align} p(x_n\vert z_{n-1}) &= \sum_{z_n=1}^{m} p(x_n,z_n\vert z_{n-1}) \\ &= \sum_{z_n=1}^{m} p(x_n\vert z_n,z_{n-1}) p(z_n\vert z_{n-1}) \\ &= \sum_{z_n=1}^{m} p(x_n\vert z_n) p(z_n\vert z_{n-1}) \end{align}\]This formula is a special case of previous more general formula where the term $p(x_{k+2:n} \vert z_{k+1})$ has become equal to 1, and if $k=n-1$ theh we’ll get $p(x_{n+1} \vert z_n) = 1$.

Summarizing all that in the final formula:

\[p(x_{k+1:n}\vert z_k) = \sum_{z_{k+1}=1}^{m} p(x_{k+2:n} \vert z_{k+1}) p(x_{k+1}\vert z_{k+1}) p(z_{k+1}\vert z_k) \\ p(x_{n+1} \vert z_n) = 1\]This is quite similar to forward part and time complexity is also $O(nm^2)$ because we have $k=1..n$ timesteps, $m$ values of $z_k$ and $z_{k+1}$ that we iterate through.

## Naive approach

To better understand the value of FB algorithm let’s just compare it with the naive approach. With conditional probability formula we know that:

\[p(z_k \vert x) = \frac{p(x,z_k)}{p(x)} \propto p(x,z_k)\]We can try directly compute $p(x,z_k)$ and for that we have to take into account all possible sequences of $z$ where $z_k$ might have been occured or in other words we should marginalize out all except $z_k$: $\hat{z} = z_1..z_{k-1},z_{k+1}..z_n$ variables:

\[\begin{align} p(x,z_k) &= \sum_{\hat{z}} p(x,z) \\ &= \sum_{z_1} \sum_{z_2} ... \sum_{z_{k-1}} \sum_{z_{k+1}} ... \sum_{z_{n}} p(x,z) \end{align}\]The number of sums is equal to number of possible permutations with repetitions of hidden state sequence $\hat{z}$ which is equal to $m^{n-1}$. This is an exponential time complexity, for $T = 101$ steps and $m = 10$ hidden states it will have $10^{100}$ terms to compute. While Forward-Backward algorithm will have $m^2 \times n = 100\times101 \approx 10^4$, that is $10^{96}$ times faster!

## Comments